Prototipe Aplikasi Ensiklopedia Indonesia Berbasis iOS - Lia Ambarwati; Sandi Agung; Soeltan Zaki; Dewi Agushinta R.; Vega Valentine (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2013)
Indonesia has a unique and interesting diversity culture as the nation's assets. Most of Indonesia people don’t know their own culture. This is because there are so many Indonesia cultures and lack of introducing them to public. The introduction of culture through reading the book is less effective. In this modern era, people more comfortable hold a smartphone, rather than to carry a book. Therefore, an easy and interesting application to introduce Indonesia culture to public is necessary. The purpose of this paper is to develop a prototype for Indonesia encyclopedia apps based iOS that can be used easily. iOS is quite popular, and fairly easy to use. The information will consist of description, demographic data, and list of culture from each Indonesia’s province. The user can select province by touching Indonesia map. The author uses object-oriented modeling, Unified Modeling Language (UML) in designing Indonesia encyclopedia applications based on iOS. Users can learn the cultures exist in Indonesia everytime and everywhere.